Randomised clinical study: the effects of oral taurine 6g/day vs placebo on portal hypertension. Issue 1 (3rd November 2017) - Schwarzer, R.; Kivaranovic, D.; Mandorfer, M.; Paternostro, R.; Wolrab, D.; Heinisch, B.; Reiberger, T.; Ferlitsch, M.; Gerner, C.; Trauner, M.; Peck‐Radosavljevic, M.; Ferlitsch, A.
Summary: Background: The amino sulphonic acid taurine reduces oxidative endoplasmatic reticulum stress and inhibits hepatic stellate cell activation, which might lead to reduction of portal pressure in cirrhosis. Aim: To assess the haemodynamic effects of taurine supplementation in patients with cirrhosis and varices. Methods: Patients with hepatic venous pressure gradient (HVPG) ≥12 mm Hg were included in this prospective proof of concept study. Concomitant nonselective beta‐blockers therapy was not allowed. Patients received either 4 weeks of oral taurine (6 g/day), or placebo, prior to evaluation of HVPG response. Results: Thirty patients were screened and 22 included in the efficacy analysis (12 taurine/10 placebo; 64% male, mean age: 52 ± 11 years, Child A: 9%, B:64%, C:27%, ascites:68%). In the taurine group, mean HVPG dropped from 20 mm Hg (±4) at baseline to 18 mm Hg (±4) on day 28 (mean relative change: −12%, P = .0093). In the placebo group, mean HVPG increased from 20 mm Hg (±5) at baseline to 21 mm Hg (±5) on day 28 (mean relative change:+2%, P = .4945). Taurine had no significant effects on systemic haemodynamics. Seven of 12 patients (58%) on taurine achieved a HVPG response >10%, compared to none in the placebo group ( P = .0053). In a multivariate linear model, HVPG reduction was significantly larger in the taurine group compared to placebo group ( P = .0091 and P = .0109 for absolute and relative change respectively). Treatment‐related adverse events included gastrointestinal discomfort and fatigue, and were usually mild and comparable between treatment groups. Conclusion: Taurine is safe and may reduce portal pressure in cirrhotic patients. More studies on the underlying mechanisms of action and long‐term effects of taurine supplementation are warranted. Abstract : Linked Content This article is linked to Ferlitsch, Dunne and Fallowfield and Srinivas papers. To view these articles visithttps://doi.org/10.1111/apt.14444, https://doi.org/10.1111/apt.14447 andhttps://doi.org/10.1111/apt.14513 .